2021
DOI: 10.1101/2021.12.13.21267718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health During COVID-19: A Qualitative Study with Ethnically Diverse Healthcare Workers in the United Kingdom

Abstract: IntroductionHealthcare workers are experiencing deterioration in their mental health due to COVID-19. Ethnic minority populations in the United Kingdom are disproportionately affected by COVID-19, with a higher death rate and poorer physical and mental health outcomes. It is important that healthcare organisations consider the specific context and mental, as well as physical, health needs of an ethnically diverse healthcare workforce in order to better support them during, and after, the COVID-19 pandemic.Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…The ethnic categorisations used and quantitative associations presented cannot fully capture the nuance of participants' lived experiences; however, complementary qualitative work in UK-REACH contextualises HCWs' individual experiences, and also highlights the role of bereavement due to COVID-19, increased clinical workloads (including the traumatic and exhausting nature of treating high volumes of sick patients), and fear of contracting or transmitting infection (including PPE access) in contributing to mental ill-health in HCWs. 21 Our finding that anxiety/depression symptoms were only weakly associated with ethnicity is similar to another study of HCW mental health during the pandemic; 5 that study also found no strong associations between ethnicity and PTSD, which may reflect its smaller sample size and lower proportion of ethnic minority participants. However, our findings are similar to the results of the NHS Staff survey 2019, 42 in which lower levels of pre-pandemic stress were generally reported by participants from Asian, Black, Chinese, and Mixed ethnic groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The ethnic categorisations used and quantitative associations presented cannot fully capture the nuance of participants' lived experiences; however, complementary qualitative work in UK-REACH contextualises HCWs' individual experiences, and also highlights the role of bereavement due to COVID-19, increased clinical workloads (including the traumatic and exhausting nature of treating high volumes of sick patients), and fear of contracting or transmitting infection (including PPE access) in contributing to mental ill-health in HCWs. 21 Our finding that anxiety/depression symptoms were only weakly associated with ethnicity is similar to another study of HCW mental health during the pandemic; 5 that study also found no strong associations between ethnicity and PTSD, which may reflect its smaller sample size and lower proportion of ethnic minority participants. However, our findings are similar to the results of the NHS Staff survey 2019, 42 in which lower levels of pre-pandemic stress were generally reported by participants from Asian, Black, Chinese, and Mixed ethnic groups.…”
Section: Discussionsupporting
confidence: 85%
“…The ethnic categorisations used and quantitative associations presented cannot fully capture the nuance of participants’ lived experiences; however, complementary qualitative work in UK-REACH contextualises HCWs’ individual experiences, and also highlights the role of bereavement due to COVID-19, increased clinical workloads (including the traumatic and exhausting nature of treating high volumes of sick patients), and fear of contracting or transmitting infection (including PPE access) in contributing to mental ill-health in HCWs. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study entitled COVID-19 anxiety among frontline nurses: predictive role of organizational support, personal resilience and social support (Qureshi et al, 2021). Anxiety-related to the COVID-19 pandemic is prevalent in the nursing workforce, potentially affecting nurses' well-being and work performance.…”
mentioning
confidence: 99%